2019
DOI: 10.3390/ijms21010123
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Osteoarthritis and BMI on Leptin Promoter Methylation in Taiwanese Adults

Abstract: Leptin (LEP) regulates glucose metabolism and energy storage in the body. Osteoarthritis (OA) is associated with the upregulation of serum LEP. LEP promoter methylation is associated with obesity. So far, few studies have explored the association of BMI and OA with LEP methylation. We assessed the interaction between body mass index (BMI) and OA on LEP promoter methylation. Data of 1114 participants comprising 583 men and 558 women, aged 30–70 years were retrieved from the Taiwan Biobank Database (2008–2015). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The most upregulated gene in our study, LEP, a weighted gene, was associated with OA and can be a new biomarker and drug target [ 46 ]. Studies have shown that plasma LEP levels are positively correlated with the risk of OA [ 47 ]. In OA patients, obesity was significantly associated with an increase in LEP promoter methylation.…”
Section: Discussionmentioning
confidence: 99%
“…The most upregulated gene in our study, LEP, a weighted gene, was associated with OA and can be a new biomarker and drug target [ 46 ]. Studies have shown that plasma LEP levels are positively correlated with the risk of OA [ 47 ]. In OA patients, obesity was significantly associated with an increase in LEP promoter methylation.…”
Section: Discussionmentioning
confidence: 99%
“…POSTN can induce the expressions of proinflammatory factors, such as MMP-9, MMP-10, and MMP-13 production, leading to degradation of the extracellular matrix [17]. LEP(Leptin)is a peptide hormone containing 167 amino acids [18]. LEP promotes the differentiation of osteoblast under normal conditions [19].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of leptin and its receptors in the synovial fluid have been reported to be higher in obese OA patients than in lean patients [ 48 ]. There was a significant association between BMI and whole blood leptin promoter methylation levels in OA patients [ 49 ]. Articular chondrocytes isolated from obese OA patients exhibit an altered response pattern to elevated leptin levels compared with lean or overweight patients [ 50 ].…”
Section: The Challenges Of Articular Cartilage Regeneration In Obesitmentioning
confidence: 99%